Corporate reputation, satisfaction, delight, and loyalty towards rural lodging units in Portugal - Loureiro, S. M. C.; Kastenholz, E. (International Journal of Hospitality Management, 2011)
This paper enriches the model of delight and satisfaction that Oliver et al. (1997) propose and Finn (2005) modifies, with a suggested causal relationship between disconfirmation and arousal and the introduction of two new variables: the lodging unit's corporate reputation and perceived quality. The modified model is applied to rural tourism accommodations in Portugal and validated using PLS (Partial Least Squares). The results suggest that the lodging unit's reputation is a more significant determinant of loyalty than satisfaction or even delight. This study further supports the conceptualization of customer delight and customer satisfaction as distinct constructs. Results may help managers of rural tourism accommodations to develop and implement more successful relationship marketing strategies.